Overdependence of Electronic Devices versus Physical Status in Preschool Children Aged from (3-6) years - Sahib, Ahmed Makki; A. Hasan, Abdul Mahdi (Journal of Neonatal Surgery, 2025)
Background: The electronic device is one of the most widely used products among adults and kids alike. Nowadays, not a single child is unaware of smartphones. Compared to adults, they can occasionally use all of its applications more skillfully. Despite the fact that children shouldn't use smartphones for extended periods of time as this could harm their health. Preschoolers' physical condition and the effects of mobile devices is a topic of growing concern in today's society. Studies have indicated that a number of variables, including television viewing, parental self-efficacy perception, and the home environment, might affect young children's nutritional intake and physical activity levels. For example, television viewing has been linked to weight status in preschool-aged children, potentially affecting their physical activity levels and eating habits. Objectives: This study aimed to assess overuse of electronic devices in preschool children aged from (3-6) years and assess overuse of electronic devices on physical status in preschool children aged from (3-6) years. Methodology: A descriptive correlation quantitative approach is used. starting from November 9th 2023 to January 12th 2025 quantitative descriptive design was employed, with data collecting included selecting (132) child are selected form Maternal and Child Health Unit services (MCHs) in Primary Health Care Centers of Al-Najaf City, Iraq. Participants were selected based on specific criteria, including the children age group was between (3 to 6) years who attained primary health center for both North and South sectors during the time of data collection for the current study, the data collected from parents who being able to read and write. Participants who had excessive use of electronic devices more than half an hour. Children who use of touchscreen devices such as smartphones or tablet computers or mobile or T.V. Problematic Technology Use Scale for Young Children (PTUS-YC) and Physical status scale (visual discomfort index, musculoskeletal discomfort index) for the child were used to measure excessive use of electronic devices levels and physical status; data were collected to analyze potential correlations. Results: The result of assessment of excessive use of electronic devices that showed mostly of preschool children (30.3%) have a high excessive use of electronic devices. While minimal physical discomfort (71.20%) impact on physical status of children as general, and minimal musculoskeletal index discomfort (72%), also minimal visual index discomfort (73.5%). Conclusion: It was noteworthy that an important number of preschool children reported excessive use of electronic devices. Mobile devices were the most used. Children's discomfort symptoms were significantly correlated with excessive use of electronic devices, as noted in the study. The analysis revealed that there is a direct relationship between excessive electronic device usage. Recommendations: Development of awareness programs and policies aimed at reducing the negative health effects of excessive electronic device use among children. Parents and guardians need to set specific rules for screen engagement for their children.